(untitled) - Gilio, Amelia K.; Abdo, Miguel A.; Martinez, Carlos A.; Palaia, Andrew T.; Livada, Jovan (Comptes Rendus. Chimie, 2025)
Biocatalysis has been used in industrial settings, especially in the pharmaceutical industry, for decades. In this review, we showcase the six most prominent enzyme classes in industrial biocatalysis: keto-reductases, ene-reductases, imine-reductases, transaminases, oxygenases, and hydrolases. For each class, several examples are presented that highlight the substrate scope and enantioselectivity of these biotransformations from milligram to multikilogram scale.